2021
DOI: 10.1186/s13613-021-00817-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of fluid responsiveness in critically ill patients mechanically ventilated at low tidal volumes: systematic review and meta-analysis

Abstract: Introduction Dynamic predictors of fluid responsiveness have shown good performance in mechanically ventilated patients at tidal volumes (Vt) > 8 mL kg−1. Nevertheless, most critically ill conditions demand lower Vt. We sought to evaluate the operative performance of several predictors of fluid responsiveness at Vt ≤ 8 mL kg−1 by using meta-regression and subgroup analyses. Methods A sensitive search was conducted in the Embase and MEDLINE datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 59 publications
1
70
1
Order By: Relevance
“…In this study, the percentage of fluid responders was 43%, which is lower than that (approximately 50%) indicated in several systematic reviews about fluid responsiveness [ 40 , 41 ]. This difference may be due to the differences in the amount of fluid infused and the definition of fluid responders.…”
Section: Discussioncontrasting
confidence: 80%
“…In this study, the percentage of fluid responders was 43%, which is lower than that (approximately 50%) indicated in several systematic reviews about fluid responsiveness [ 40 , 41 ]. This difference may be due to the differences in the amount of fluid infused and the definition of fluid responders.…”
Section: Discussioncontrasting
confidence: 80%
“…However, several studies which clearly demonstrated the validity of the EEO test had included ventilated patients with a Vt less than 8 mL/kg, and even less than 7 mL/kg [ 42 , 53 ]. This was even recently confirmed by a meta-analysis that only included studies performed under conditions of low Vt [ 54 ]. In addition, the EEO test has been shown to be reliable regardless of the level of respiratory driving pressure [ 55 ].…”
Section: End-expiratory Occlusion Testmentioning
confidence: 71%
“…The Vt challenge has been validated by far fewer studies than the PLR test, for example, although its reliability has been confirmed in a recent meta-analysis [ 54 ]. Moreover, the diagnostic thresholds differ slightly between the few available studies (Table 2 ), which in addition expressed the change in PPV either as an absolute value [ 30 , 52 , 65 ]} or as a percent change [ 56 , 66 , 67 ], or both [ 29 ].…”
Section: Tidal Volume Challengementioning
confidence: 99%
See 1 more Smart Citation
“…As such, POCUS measurements of the IVC size and collapsibility index have been used to assess volume status [ 8 , 9 ] and have been studied extensively in ICU patients [ 10 ]. POCUS is clearly less invasive than traditional measurements of fluid status, such as central venous pressure or pulmonary arterial catheter measurements.…”
Section: Focused Cardiac Ultrasound To Assess Cardiovascular Statusmentioning
confidence: 99%